Prosodic Cues Used During Perceptions of Nonunderstandings in Radio Communication. (11th May 2013) - Auton, Jaime C.; Wiggins, Mark W.; Searle, Ben J.; Loveday, Thomas; Rattanasone, Nan Xu
<x xml:space="preserve">Abstract</x> The readback/hearback protocol is a radio procedure intended to reduce communication errors in technical industries. It consists of the delivery of an instruction to a receiver, and the readback of that instruction by the receiver to confirm to the sender that it has been heard accurately. It does not, however, ensure that the receiver has understood the instruction. Using 2 samples within electricity transmission control, the present research explored whether the prosodic cues that listeners use to interpret uncertainty are also used to judge whether a receiver is perceived to have understood an instruction. Rising intonation and filled interturn delays were identified as prosodic cues that operators use to identify nonunderstandings. Theoretical and practical implications of the findings are considered.